Revision of the Nearctic species of the genus Iphthiminus Spilman (Coleoptera: Tenebrionidae) - Gardiner, Rebekka M.; Pollock, Darren A. (Zootaxa, 2015)
Nearctic species of Iphthiminus Spilman (Coleoptera: Tenebrionidae) are revised by examining external morphological structures and genital characters. Of the six Nearctic species, only three are considered valid: Iphthiminus serratus (Mannerheim 1843), I. opacus (Leconte 1866), and I. lewisii (Horn 1870). Photographs are taken to highlight structures and a key is created to identify the species. Three names are synonymized: (senior synonym in brackets) I. sublaevis (Bland 1865) [=Nyctobates sublaevis (Bland 1865)], I. salebrosus (Casey 1924) [=Iphthimus salebrosus (Casey 1924)] are synonymized under I. serratus (Mannerheim 1843) [=Nyctobates serratus (Mannerheim 1843)], and I. laevissimus (Casey 1890 [=Iphthimus laevissimus (Casey 1890)] is synonymized under Iphthiminus lewisii (Horn 1870) [=Iphthimus lewisii (Horn 1870)]. Lectotypes are designated for Iphthimus serratus lewisii Horn 1870 and Iphthimus opacus LeConte 1866.